2017
DOI: 10.1021/acs.jproteome.7b00127
|View full text |Cite
|
Sign up to set email alerts
|

Aggregatibacter actinomycetemcomitans Growth in Biofilm versus Planktonic State: Differential Expression of Proteins

Abstract: Aggregatibacter actinomycetemcomitans (Aa) is a pathogenic bacterium residing in the subgingival plaque biofilm strongly associated with the pathogenesis of periodontitis. The aim of this investigation was to study the protein differential expression of Aa when growing on biofilm compared with planktonic state using proteomic analysis by the 2D-DIGE system. Eighty-seven proteins were differentially expressed during biofilm growth (1.5-fold, p < 0.05), with 13 overexpressed and 37 down-expressed. Those represse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 72 publications
1
19
0
1
Order By: Relevance
“…Differential gene expressions between A. actinomycetemcomitans in its planktonic and biofilm states had been observed previously [44], and our study confirmed their observations on several genes. The gene PTS mannose transporter subunit IIAB (D7S_01753) was found to be upregulated by both studies.…”
Section: Discussionsupporting
confidence: 92%
“…Differential gene expressions between A. actinomycetemcomitans in its planktonic and biofilm states had been observed previously [44], and our study confirmed their observations on several genes. The gene PTS mannose transporter subunit IIAB (D7S_01753) was found to be upregulated by both studies.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it is a useful tool to study how A. actinomycetemcomitans orchestrates proteomic changes in the context of biofilms. Using 2D gels, Llama-Palacios et al discovered 87 protein spots differently expressed (1.5-fold, p < 0.05) between planktonic and mono-species biofilm cultures of A. actinomycetemcomitans [171]. Then, using MALDI-TOF MS, 13 upregulated proteins (from 24 proteins spots) and 37 downregulated proteins (from 50 spots) were identified.…”
Section: Localization In Biofilms and Proteomic Interactions With Othmentioning
confidence: 99%
“…These outer membrane vesicles contain many effector proteins that are internalized into human host cells. 67,73 including the ability to attain a more realistic representation of the cell state, 76 the ability to connect various pathways via the observation of pathway intermediates, [84][85][86] and an unbiased evaluation of the cell state under specific conditions. 87,88 Monitoring metabolite profiles in body fluids to understand disease etiology has been a common focus of this approach.…”
Section: Proteomic In Vitro Studiesmentioning
confidence: 99%